Prospective Teachers’ Scientific Literacy through Ethnoscience Learning Integrated with the Indigenous Knowledge of People in the Frontier, Outermost, and Least Developed Regions - Parmin, Parmin; Fibriana, Fidia (Jurnal Penelitian dan Pembelajaran IPA, 2019)
The indigenous knowledge in the frontier, outermost, and least developed regions has not been explored thoroughly as an application for Ethnoscience learning. Therefore, this research aimed to explore the indigenous knowledge and its application to measure prospective science teachers’ scientific literacy through Ethnoscience learning. The prospective science teachers joining the Ethnoscience subject were employed as the research samples. A descriptive research method with a qualitative approach was applied for this study. The indigenous knowledge in the frontier, outermost, and least developed regions, i.e., Sumatra, Java, Sulawesi, Kalimantan, and Papua, is a potential learning source for exciting science learning and providing the opportunity for prospective science teachers to develop scientific literacy. Based on the results, 13 students achieved grade A, whereas 14 students got AB, and the other 4 students achieved B. All prospective science teachers were good at analytical thinking, problem-solving, and communicating. They also gained knowledge from the analysis results, which made them master the problem-solving skill. In conclusion, the indigenous knowledge of the frontier, outermost, and least regions integrated with Ethnoscience learning can improve the prospective science teachers’ scientific literacy effectively.